Pengembangan buku ajar mata kuliah belajar dan pembelajaran berbasis moodle - Anangga Widya Pradipta; Rubbi Kurniawan (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Belajar dan Pembelajaran (learning and teaching learning) requires high analytical skills, flexible time, and supporting learning media, one of which is books. This research aims to design and develop teaching books for Belajar dan Pembelajaran that are MOODLE-based. This research employed Research and Development (R&D) method with the ADDIE technique. Participants of this research are second-semester students of the PJKR IKIP Budi Utomo Program (the year 2019-2020) who took the Belajar dan Pembelajaran course. Questionnaire technique was employed to determine the feasibility of teaching books, and to test student learning outcomes after using MOODLE-based teaching books. The standard assessment of content from media experts is 57 with a percentage of 95%, referring to very good criteria without revision. The visual standard assessment from media experts is 61 with a percentage of 94%, referring to very good criteria without revision. The content standard assessment from material experts is 48 with a percentage of 80%, referring to very good criteria without revision. The visual standard assessment from material experts is 53 with a percentage of 82%, referring to very good criteria without revision. Teaching books’ effectiveness (N-gain) is 0.52 on moderate criteria.